Verb forms in medieval Anglo-Irish texts - Jakubowski, Piotr (Adam Mickiewicz University, 2006)
The object of the present study is the shift of strong to weak verbs in medieval Irish English of the fourteenth century as represented by the text of the Kildare Poems. A comparison with the developments in other dialects of English of the same period reveals a degree of conservatism in Irish English. In fact, some of the verbs which either became weak or developed parallel weak forms remain strong in the Irish English dialect. The forms which retained the strong pattern are discussed in detail and are provided as evidence of the archaic character of Irish English.